Stanisław Keturakis – Litwin w służbie rosyjskiej oświaty na terenie guberni piotrkowskiej w latach 1895–1914 - Złotkowski, Dariusz (Biuletyn Historii Wychowania, 2020)
At the end of the 19th century, the teaching profession was the aspiration of many peasant sons. The position of a teacher ensured a modest but quite stable income. A Lithuanian, born in 1989, Stanislaw Keturakis, was one of graduates of the Teachers’ College in Wejwery near Kaunas. This institution offered a state scholarship. In return for this financial help, its graduates had to accept posts in primary schools determined by educational authorities. A few graduates of this school, mostly Lithuanians, were sent to work in village schools of Piotrków province. One of them, Stanislaw Keturakis, began his first teaching job in a school in Jedlno. He was confronted with difficult living conditions, the school was only planned to be built. At this time, he married Józefa Birsztejn and they had two sons: Eugeniusz Józef (1901) and Zdzisław Aleksander (1904). Peasants perceived teachers as tsarist officials. In 1901, S. Keturakis was transferred to Mstów, to work as a teacher, then to Wancerzów, and again back to Jedlno. Taking over a position of a teacher in Zagórze (1907) was clearly a promotion. The school belonged to the private property of Grand Duke Michael Alexandrovich of Russia, a brother of Emperor Nicholas II. The last stage of S. Keturakis’s teaching career was his work in a school in Zagórze. Working there in the years 1907–1914, he taught Russian, Polish, Arithmetic, History and Geography. At the end of the summer 1914, he got an opportunity to take over the post of the forester’s assistant in Orłow province, but the outbreak of the war made it impossible. Lack of any sources does not allow us to determine what the further life of Stanislaw Keturakis was like.